Postmortem evidence of disseminated Zika virus infection in an adult patient. (June 2019) - Rajahram, Giri Shan; Hale, Gillian; Bhatnagar, Julu; Hiu, Jessie; Thayan, Ravindran; William, Timothy; Wong, Kum Thong; Tambyah, Paul Anantharajah; Yeo, Tsin Wen
Highlights: Zika virus (ZIKV) infections in immunocompetent adults are typically asymptomatic or cause mild symptoms. ZIKV-associated non-neurological fatalities in adults are rare. We describe a fatal case in a patient with multiple comorbidities, who developed an acute febrile illness with rash days prior to death. Detailed postmortem evaluation detected molecular evidence of disseminated ZIKV. ZIKV in situ hybridization identified genomic and replicative ZIKV RNA in renal tubular epithelial cells and cardiomyocytes, providing insights into organ-specific viral reservoirs.